A flux core material, a stainless steel welding wire containing the flux core material, and a method for preparing the welding wire
By using flux core materials with specific raw material ratios to prepare stainless steel welding wire, the existing welding wire has been solved, the problems of low welding efficiency, poor quality and high cost are achieved, and the performance of the weld is improved.
Patent Information
- Application Number
- CN202211584571.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The existing stainless steel welding wires have problems such as low welding efficiency, poor welding quality and high welding cost during welding.
A medicinal material containing a specific raw material ratio includes rutile, reduced iron powder, microcarbon ferrochromium, metal chromium, zircon sand, manganese metal, nickel powder, feldspar, ice crystal, potassium fluorosilicate, fluoride Rare earths and Teflon, stainless steel wires are prepared through specific drying and mixing processes.
It improves welding efficiency, ensures good quality of welds, reduces welding costs, and improves the pore and crack resistance of welds.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding wires, in particular to a flux core material, a stainless steel welding wire containing the flux core material and a method for preparing the welding wire. Background Art
[0002] Stainless steel is a type of steel material, which has the characteristics of good corrosion resistance, high strength, high temperature oxidation resistance and high strength. In addition, stainless steel has good room temperature processing performance and high surface finish. Therefore, stainless steel is widely used in petrochemical, light industry food, pharmaceutical and other industries. Due to the good welding performance of stainless steel, welding is often used to fix and connect stainless steel in the processing process. However, when welding stainless steel, the existing welding wire has problems such as low welding efficiency, poor welding quality and high welding cost. Summary of the invention
[0003] The object of the present invention is to provide a flux core material, a stainless steel welding wire containing the flux core material and a method for preparing the welding wire. The stainless steel welding wire prepared using the flux core material has high welding efficiency, good welding quality and low welding cost.
[0004] To meet the above-mentioned technical objectives and related technical objectives, the present invention provides a core material, which includes the following raw materials in parts by weight: 5 to 10 parts of rutile, 20 to 30 parts of reduced iron powder, 15 to 20 parts of micro-carbon ferrochrome, 10 to 15 parts of metallic chromium, 10 to 20 parts of zircon sand, 3 to 6 parts of metallic manganese, 6 to 12 parts of nickel powder, 3 to 6 parts of feldspar, 0.5 to 2 parts of cryolite, 0.1 to 0.5 parts of potassium fluorosilicate, 0.1 to 0.6 parts of rare earth fluoride, and 0.1 to 0.3% of Teflon based on the total mass of the core material.
[0005] In one example of the drug core material of the present invention, the rutile is 5 to 7 parts.
[0006] In one example of the core material of the present invention, the reduced iron powder is 20 to 26 parts.
[0007] In one example of the core material of the present invention, the micro-carbon ferrochromium is 15 to 17 parts.
[0008] In one example of the core material of the present invention, the metal chromium is 10 to 13 parts.
[0009] In one example of the core material of the present invention, the zircon sand is 19 to 20 parts.
[0010] In one example of the core material of the present invention, the metal manganese is 5 to 6 parts.
[0011] In one example of the core material of the present invention, the nickel powder is 10 to 12 parts.
[0012] In one example of the core material of the present invention, the feldspar is 3 to 5 parts.
[0013] In one example of the core material of the present invention, the cryolite is 1 to 2 parts.
[0014] In one example of the drug core material of the present invention, the potassium fluorosilicate is 0.3 to 0.5 parts.
[0015] In one example of the drug core material of the present invention, the rare earth fluoride is 0.4 to 0.6 parts.
[0016] In an example of the drug core material of the present invention, the added amount of Teflon is 0.2-0.3% based on the total mass of the drug core material.
[0017] In one example of the drug core material of the present invention, the particle size of the rutile is 70-80 mesh.
[0018] In one example of the core material of the present invention, the particle size of the reduced iron powder is 60-70 meshes.
[0019] In one example of the core material of the present invention, the particle size of the micro-carbon ferrochrome is 70-80 mesh.
[0020] In one example of the core material of the present invention, the particle size of the metal chromium is 70-80 mesh.
[0021] In one example of the core material of the present invention, the particle size of the zircon sand is 60-70 mesh.
[0022] In one example of the core material of the present invention, the particle size of the metal manganese is 70-80 mesh.
[0023] In one example of the core material of the present invention, the particle size of the nickel powder is 60-70 mesh.
[0024] In one example of the core material of the present invention, the particle size of the feldspar is 70-80 mesh.
[0025] In one example of the core material of the present invention, the particle size of the cryolite is 70-80 mesh.
[0026] In one example of the drug core material of the present invention, the particle size of the potassium fluorosilicate is 60-70 mesh.
[0027] In one example of the drug core material of the present invention, the particle size of the rare earth fluoride is 60-70 mesh.
[0028] In one example of the drug core material of the present invention, the particle size of the Teflon is 70-80 mesh.
[0029] The present invention also provides a stainless steel welding wire, which includes a steel strip sheath and a flux core, wherein the flux core is made of the above-mentioned flux core material, and the flux core material is filled in the steel strip sheath, and the steel strip sheath is a 308L stainless steel strip. Based on the total mass of the 308L stainless steel strip, the 308L stainless steel strip includes the following components in percentage by mass: C: ≤0.03%, Mn: ≤2.00%, Si: ≤1.00%, Cr: 19.0-21.0%, Ni: 10.0-12.5%, P: ≤0.045%, S: ≤0.03%, and the remainder is Fe and unavoidable impurities.
[0030] In an example of a stainless steel welding wire of the present invention, the filling factor of the flux core material is 20-25%.
[0031] The present invention also provides a method for preparing a stainless steel welding wire, wherein the flux core of the stainless steel welding wire is made of the above-mentioned flux core material, and the preparation steps include:
[0032] S1, drying the components of the drug core material for the first time, adding the drug core material after the first drying into a powder mixer and stirring and mixing evenly, and then drying the evenly mixed drug core material for the second time to obtain a drug core material dry powder mixture;
[0033] S2, rolling the steel strip into a U-shaped groove;
[0034] S3, filling the drug core material dry powder mixture into the U-shaped groove;
[0035] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material, rolling it into an O-shape, and then drawing it to a set diameter of the stainless steel welding wire.
[0036] In an example of the method for preparing the stainless steel welding wire of the present invention, in step S1, the temperature for the first drying of rutile, zircon sand, feldspar and cryolite is 900-950°C, and the drying time is 10-12 hours, and the temperature for the first drying of reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon is 250-350°C, and the drying time is 10-15 hours.
[0037] In an example of the method for preparing the stainless steel welding wire of the present invention, in step S1, the temperature for the second drying of the uniformly mixed flux core material is 100-150° C., and the drying time is 1-2 hours.
[0038] The functions of the components in the drug core material of the present invention are as follows:
[0039] Rutile: Main component is TiO 2, is the main slag-forming agent. Adding an appropriate amount can stabilize the welding arc, reduce spatter, improve slag fluidity, and facilitate all-position welding operations. When the amount added is too small, the above characteristics are not obvious. When the amount added is too much, there is too much slag, which is difficult to remove, and the oxygen content of the weld will increase, which is not conducive to the mechanical properties of the deposited metal.
[0040] Micro-carbon ferrochrome: It acts as an alloying agent to ensure that the Cr in the deposited metal is within the required range. The Cr element can improve the hardenability of the weld metal and increase the hardness and tensile yield strength of the weld metal. The chemical composition of micro-carbon ferrochrome includes Cr: 63.0~75.0, C≤0.03, Si≤1.0, P≤0.03, S≤0.025.
[0041] Metallic chromium: acts as an alloying agent to ensure that the Cr content of the deposited metal is within the required range. The Cr element can improve the hardenability of the weld metal and increase the hardness and tensile yield strength of the weld metal.
[0042] Zircon sand: The main component is ZrO 2 and SiO2, play the role of slag-forming agent, adding a proper amount can stabilize the welding arc, reduce spatter, improve the fluidity of slag, and facilitate all-position welding operation. When the amount added is too small, the above characteristics are not obvious, and when the amount added is too much, there is too much slag, which is not easy to remove, and the oxygen content of the weld will increase, which is not conducive to the mechanical properties of the deposited metal.
[0043] Metallic manganese: Its main function is as a deoxidizer. In addition, it can also act as an alloying agent to ensure that the Mn content of the deposited metal is within a certain range. Mn has a strong solid solution strengthening and desulfurization effect. Adding Mn can reduce the temperature of the phase transition from γ phase to α phase and promote AF transformation. Therefore, an appropriate amount of Mn can improve the strength and toughness of the weld metal.
[0044] Nickel powder: acts as an alloying agent to ensure that the Ni in the deposited metal is within the required range, and forms a certain proportion with the chromium, manganese, silicon and other elements in the weld, controls the content of ferrite in the weld, and makes the weld have better crack resistance and corrosion resistance.
[0045] Feldspar: It plays the role of slag-forming agent. Adding a proper amount can stabilize the welding arc, reduce spatter, and improve the fluidity of slag. When the amount added is too small, the above characteristics are not obvious. When the amount added is too much, it is not easy to remove the slag, and the oxygen content of the weld will increase, which is not conducive to the mechanical properties of the deposited metal.
[0046] Cryolite: Adding an appropriate amount of cryolite can improve the fluidity of the slag. If too much is added, it will lead to increased welding spatter.
[0047] Potassium fluorosilicate: Adding an appropriate amount of potassium fluorosilicate can improve the fluidity of the slag. If too much is added, it will lead to increased welding spatter.
[0048] Rare earth fluoride: Adding an appropriate amount of rare earth fluoride can improve the fluidity of the slag and improve slag removal. If too much is added, it will lead to increased welding spatter.
[0049] Teflon: Adding an appropriate amount of Teflon can reduce welding spatter. It can also improve the fluidity of powder, which is beneficial to the smooth wire drawing production.
[0050] Reduced iron powder: acts as a filler to ensure that the filled powder is densely filled inside the flux-cored welding wire without flowing.
[0051] In summary, in the flux core material and the stainless steel welding wire and the preparation method of the welding wire containing the flux core material of the present invention, the joint effect of Teflon and rare earth fluoride can effectively improve the anti-porosity and anti-cracking performance of the weld, and the joint effect of cryolite and potassium fluorosilicate can improve the anti-porosity and slag removal performance of the welding wire. As a result, the welding efficiency of the stainless steel welding wire is high, the weld is bright and beautiful, the deposited metal has no pores and sand holes, the weld surface is easy to remove slag, and the deposited metal has good strength and corrosion resistance. DETAILED DESCRIPTION
[0052] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0053] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0054] It should also be noted that the material components not specifically described in the present invention are all selected from conventional raw materials in the field of welding wire technology and can be obtained through general commercial channels. Except for the explicitly given values in the following embodiments, other unpublished conditions are the same.
[0055] The following will be described with specific embodiments. In the following embodiments, in an example of the core material of the present invention, the particle size of the rutile is 70-80 mesh, the particle size of the reduced iron powder is 60-70 mesh, the particle size of the micro-carbon ferrochrome is 70-80 mesh, the particle size of the metallic chromium is 70-80 mesh, the particle size of the zircon sand is 60-70 mesh, the particle size of the metallic manganese is 70-80 mesh, the particle size of the nickel powder is 60-70 mesh, the particle size of the feldspar is 70-80 mesh, the particle size of the cryolite is 70-80 mesh, the particle size of the potassium fluorosilicate is 60-70 mesh, the particle size of the rare earth fluoride is 60-70 mesh, and the particle size of the Teflon is 70-80 mesh.
[0056] The invention provides a core material, which comprises the following raw materials in parts by weight: 5 to 10 parts of rutile, 20 to 30 parts of reduced iron powder, 15 to 20 parts of micro-carbon ferrochrome, 10 to 15 parts of metallic chromium, 10 to 20 parts of zircon sand, 3 to 6 parts of metallic manganese, 6 to 12 parts of nickel powder, 3 to 6 parts of feldspar, 0.5 to 2 parts of cryolite, 0.1 to 0.5 parts of potassium fluorosilicate, 0.1 to 0.6 parts of rare earth fluoride, and 0.1 to 0.3% of Teflon based on the total weight of the core material.
[0057] The present invention also provides a stainless steel welding wire, which comprises a steel strip outer skin and a flux core, wherein the flux core is made of the above-mentioned flux core material, and the flux core material is filled in the steel strip outer skin, wherein the steel strip outer skin is a 308L stainless steel strip, and based on the total mass of the 308L stainless steel strip, the 308L stainless steel strip comprises the following components in mass percentage: C: ≤0.03%, Mn: ≤2.00%, Si: ≤1.00%, Cr: 19.0-21.0%, Ni: 10.0-12.5%, P: ≤0.045%, S: ≤0.03%, and the remainder is Fe and unavoidable impurities. The filling coefficient of the flux core material is 20-25%.
[0058] Filling factor = mass of core material dry powder mixture ÷ total mass of stainless steel welding wire.
[0059] The present invention also provides a method for preparing a stainless steel welding wire, wherein the flux core of the stainless steel welding wire is made of the above-mentioned flux core material, and the preparation steps include:
[0060] S1, drying the components of the drug core material for the first time, adding the drug core material after the first drying into a powder mixer and stirring and mixing evenly, and then drying the evenly mixed drug core material for the second time to obtain a drug core material dry powder mixture;
[0061] S2, rolling the steel strip into a U-shaped groove;
[0062] S3, filling the drug core material dry powder mixture into the U-shaped groove;
[0063] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material, rolling it into an O-shape, and then drawing it to a set diameter of the stainless steel welding wire.
[0064] In an example of the method for preparing the stainless steel welding wire of the present invention, in step S1, the temperature for the first drying of rutile, zircon sand, feldspar and cryolite is 900-950°C, and the drying time is 10-12 hours, and the temperature for the first drying of reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon is 250-350°C, and the drying time is 10-15 hours.
[0065] In an example of the method for preparing the stainless steel welding wire of the present invention, in step S1, the temperature for the second drying of the uniformly mixed flux core material is 100-150° C., and the drying time is 1-2 hours.
[0066] Example 1
[0067] A core material comprises the following raw materials in parts by weight: 5 parts of rutile, 20 parts of reduced iron powder, 15 parts of micro-carbon ferrochrome, 15 parts of metallic chromium, 20 parts of zircon sand, 6 parts of metallic manganese, 6 parts of nickel powder, 3 parts of feldspar, 0.5 parts of cryolite, 0.1 parts of potassium fluorosilicate, 0.1 parts of rare earth fluoride, and 0.1% of Teflon based on the total weight of the core material.
[0068] The above-mentioned flux core material is used to prepare a stainless steel welding wire, and the preparation steps include:
[0069] S1. Dry rutile, zircon sand, feldspar and cryolite for the first time at 900°C for 12 hours, dry reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon for the first time at 250°C for 15 hours, add the core material after the first drying into a powder mixer and stir to mix evenly, then dry the evenly mixed core material for the second time at 150°C for 1 hour to obtain a core material dry powder mixture, and obtain a core material dry powder mixture.
[0070] S2. The outer skin of the steel strip is 308L stainless steel strip with a thickness of 0.3mm and a width of 10mm. The outer skin of the steel strip is cut longitudinally, wrapped with a strip, and then cleaned with a cleaning liquid and rolled into a U-shaped groove.
[0071] S3, filling the drug core material dry powder mixture into the U-shaped groove.
[0072] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material and rolling it into an O-shape, and then obtaining the stainless steel welding wire after welding, scar scraping, wire drawing and reducing diameter, layer winding and other operations.
[0073] Wherein, the filling factor of the flux core material in the stainless steel welding wire is 20%.
[0074] The stainless steel welding wire prepared in this embodiment is used for test plate welding, the welding current is 240A, the welding voltage is 30V, the shielding gas is 100% CO2, the wind speed is 0.2m / s, the tensile strength of the welded metal is 605MPa, the yield strength is 470MPa, the elongation is 41%, the impact absorption energy at -40℃ is 80J, the diffusible hydrogen content is 5ml / 100g, the X-ray flaw detection result is no pores, the film evaluation grade is 1, the intergranular corrosion test is performed on the welded test plate with copper sulfate, the test plate is taken out and then subjected to a bending test, there is no crack at the weld, and the corrosion resistance test is passed. It is proved that the stainless steel welding wire of the present invention has good strength and corrosion resistance, as well as anti-pore ability.
[0075] Example 2
[0076] A core material comprises the following raw materials in parts by weight: 6 parts of rutile, 23 parts of reduced iron powder, 16 parts of micro-carbon ferrochrome, 14 parts of metallic chromium, 19 parts of zircon sand, 5 parts of metallic manganese, 8 parts of nickel powder, 4 parts of feldspar, 0.8 parts of cryolite, 0.2 parts of potassium fluorosilicate, 0.2 parts of rare earth fluoride, and 0.1% of Teflon based on the total weight of the core material.
[0077] The above-mentioned flux core material is used to prepare a stainless steel welding wire, and the preparation steps include:
[0078] S1. Dry rutile, zircon sand, feldspar and cryolite for the first time at 950°C for 10 hours, dry reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon for the first time at 350°C for 10 hours, add the core material after the first drying into a powder mixer and stir to mix evenly, then dry the evenly mixed core material for the second time at 100°C for 2 hours to obtain a core material dry powder mixture, and obtain a core material dry powder mixture.
[0079] S2. The outer skin of the steel strip is 308L stainless steel strip with a thickness of 0.3mm and a width of 10mm. The outer skin of the steel strip is cut longitudinally, wrapped with a strip, and then cleaned with a cleaning liquid and rolled into a U-shaped groove.
[0080] S3, filling the drug core material dry powder mixture into the U-shaped groove.
[0081] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material and rolling it into an O-shape, and then obtaining the stainless steel welding wire after welding, scar scraping, wire drawing and reducing diameter, layer winding and other operations.
[0082] Wherein, the filling factor of the flux core material in the stainless steel welding wire is 23%.
[0083] The stainless steel welding wire prepared in this embodiment is used for test plate welding, the welding current is 240A, the welding voltage is 30V, the shielding gas is 100% CO2, the wind speed is 0.2m / s, the tensile strength of the welded metal is 620MPa, the yield strength is 485MPa, the elongation is 40%, the impact absorption energy at -40℃ is 76J, the diffusible hydrogen content is 5ml / 100g, the X-ray flaw detection result is no pores, the film evaluation grade is 1, the intergranular corrosion test is performed on the welded test plate with copper sulfate, the test plate is taken out and then subjected to a bending test, there is no crack at the weld, and the corrosion resistance test is passed. It is proved that the stainless steel welding wire of the present invention has good strength and corrosion resistance, as well as anti-pore ability.
[0084] Example 3
[0085] A core material comprises the following raw materials in parts by mass: 7 parts of rutile, 26 parts of reduced iron powder, 17 parts of micro-carbon ferrochrome, 13 parts of metallic chromium, 20 parts of zircon sand, 3 parts of metallic manganese, 10 parts of nickel powder, 5 parts of feldspar, 1 part of cryolite, 0.3 parts of potassium fluorosilicate, 0.4 parts of rare earth fluoride, and 0.2% of Teflon based on the total mass of the core material.
[0086] The above-mentioned flux core material is used to prepare a stainless steel welding wire, and the preparation steps include:
[0087] S1. Dry rutile, zircon sand, feldspar and cryolite for the first time at 900°C for 12 hours, dry reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon for the first time at 250°C for 15 hours, add the core material after the first drying into a powder mixer and stir to mix evenly, then dry the evenly mixed core material for the second time at 150°C for 1 hour to obtain a core material dry powder mixture, and obtain a core material dry powder mixture.
[0088] S2. The outer skin of the steel strip is 308L stainless steel strip with a thickness of 0.3mm and a width of 10mm. The outer skin of the steel strip is cut longitudinally, wrapped with a strip, and then cleaned with a cleaning liquid and rolled into a U-shaped groove.
[0089] S3, filling the drug core material dry powder mixture into the U-shaped groove.
[0090] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material and rolling it into an O-shape, and then obtaining the stainless steel welding wire after welding, scar scraping, wire drawing and reducing diameter, layer winding and other operations.
[0091] Wherein, the filling factor of the flux core material in the stainless steel welding wire is 24%.
[0092] The stainless steel welding wire prepared in this embodiment is used for test plate welding, the welding current is 240A, the welding voltage is 30V, the shielding gas is 100% CO2, the wind speed is 0.2m / s, the tensile strength of the welded metal is 615MPa, the yield strength is 480MPa, the elongation is 41%, the impact absorption energy at -40℃ is 78J, the diffusible hydrogen content is 5ml / 100g, the X-ray flaw detection result is no pores, the film evaluation grade is 1, the intergranular corrosion test is performed on the welded test plate with copper sulfate, the test plate is taken out and then subjected to a bending test, there is no crack at the weld, and the corrosion resistance test is passed. It is proved that the stainless steel welding wire of the present invention has good strength and corrosion resistance, as well as anti-pore ability.
[0093] Example 4
[0094] A core material comprises the following raw materials in parts by weight: 10 parts of rutile, 30 parts of reduced iron powder, 20 parts of micro-carbon ferrochrome, 11 parts of metallic chromium, 20 parts of zircon sand, 6 parts of metallic manganese, 12 parts of nickel powder, 6 parts of feldspar, 2 parts of cryolite, 0.5 parts of potassium fluorosilicate, 0.6 parts of rare earth fluoride, and 0.3% of Teflon based on the total weight of the core material.
[0095] The above-mentioned flux core material is used to prepare a stainless steel welding wire, and the preparation steps include:
[0096] S1. Dry rutile, zircon sand, feldspar and cryolite for the first time at 900°C for 12 hours, dry reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon for the first time at 250°C for 15 hours, add the core material after the first drying into a powder mixer and stir to mix evenly, then dry the evenly mixed core material for the second time at 150°C for 1 hour to obtain a core material dry powder mixture, and obtain a core material dry powder mixture.
[0097] S2. The outer skin of the steel strip is 308L stainless steel strip with a thickness of 0.3mm and a width of 10mm. The outer skin of the steel strip is cut longitudinally, wrapped with a strip, and then cleaned with a cleaning liquid and rolled into a U-shaped groove.
[0098] S3, filling the drug core material dry powder mixture into the U-shaped groove.
[0099] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material and rolling it into an O-shape, and then obtaining the stainless steel welding wire after welding, scar scraping, wire drawing and reducing diameter, layer winding and other operations.
[0100] Wherein, the filling factor of the flux core material in the stainless steel welding wire is 25%.
[0101] The stainless steel welding wire prepared in this embodiment is used for test plate welding, the welding current is 240A, the welding voltage is 30V, the shielding gas is 100% CO2, the wind speed is 0.2m / s, the tensile strength of the welded metal is 610MPa, the yield strength is 475MPa, the elongation is 41%, the impact absorption energy at -40℃ is 74J, the diffusible hydrogen content is 5ml / 100g, the X-ray flaw detection result is no pores, the film evaluation grade is 1, the intergranular corrosion test is performed on the welded test plate with copper sulfate, the test plate is taken out and then subjected to a bending test, there is no crack at the weld, and the corrosion resistance test is passed. It is proved that the stainless steel welding wire of the present invention has good strength and corrosion resistance, as well as anti-pore ability.
[0102] Example 5
[0103] A core material comprises the following raw materials in parts by mass: 5 parts of rutile, 20 parts of reduced iron powder, 15 parts of micro-carbon ferrochrome, 10 parts of metallic chromium, 10 parts of zircon sand, 6 parts of metallic manganese, 6 parts of nickel powder, 3 parts of feldspar, 0.5 parts of cryolite, 0.1 parts of potassium fluorosilicate, 0.1 parts of rare earth fluoride, and 0.1% of Teflon based on the total mass of the core material.
[0104] The above-mentioned flux core material is used to prepare a stainless steel welding wire, and the preparation steps include:
[0105] S1. Dry rutile, zircon sand, feldspar and cryolite for the first time at 950°C for 10 hours, dry reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon for the first time at 350°C for 10 hours, add the core material after the first drying into a powder mixer and stir to mix evenly, then dry the evenly mixed core material for the second time at 100°C for 2 hours to obtain a core material dry powder mixture, and obtain a core material dry powder mixture.
[0106] S2. The outer skin of the steel strip is 308L stainless steel strip with a thickness of 0.3mm and a width of 10mm. The outer skin of the steel strip is cut longitudinally, wrapped with a strip, and then cleaned with a cleaning liquid and rolled into a U-shaped groove.
[0107] S3, filling the drug core material dry powder mixture into the U-shaped groove.
[0108] S4, closing the U-shaped groove containing the dry powder mixture of the flux core material and rolling it into an O-shape, and then obtaining the stainless steel welding wire after welding, scar scraping, wire drawing and reducing diameter, layer winding and other operations.
[0109] Wherein, the filling factor of the flux core material in the stainless steel welding wire is 25%.
[0110] The stainless steel welding wire prepared in this embodiment is used for test plate welding, the welding current is 240A, the welding voltage is 30V, the shielding gas is 100% CO2, the wind speed is 0.2m / s, and the tensile strength of the weld deposited metal is measured to be 625MPa, the yield strength is 485MPa, the elongation is 41%, the -40°C impact absorption energy is 72J, the diffusible hydrogen content is 5ml / 100g, the X-ray flaw detection result is no pores, and the film evaluation grade is 1. The intergranular corrosion test of the test plate after welding is performed with copper sulfate, and the test plate is taken out and subjected to a bending test. There are no cracks at the weld. The corrosion resistance test proves that the stainless steel welding wire of the present invention has good strength and corrosion resistance, as well as anti-pore ability.
[0111] The present invention utilizes the combined effect of Teflon and rare earth fluoride to effectively improve the anti-porosity and anti-cracking performance of the weld, and the combined effect of cryolite and potassium fluorosilicate can improve the anti-porosity and slag removal performance of the welding wire. As a result, the welding efficiency of the stainless steel welding wire is high, the weld is bright and beautiful, the deposited metal has no pores and sand holes, the slag removal of the weld surface is easy, and the deposited metal has good strength and corrosion resistance.
[0112] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A drug core material, characterized in that: The invention is composed of the following raw materials in parts by weight: 5 to 10 parts of rutile, 20 to 30 parts of reduced iron powder, 15 to 20 parts of micro-carbon ferrochrome, 10 to 15 parts of metallic chromium, 10 to 20 parts of zircon sand, 3 to 6 parts of metallic manganese, 6 to 12 parts of nickel powder, 3 to 6 parts of feldspar, 0.5 to 2 parts of cryolite, 0.1 to 0.5 parts of potassium fluorosilicate, 0.1 to 0.6 parts of rare earth fluoride, and 0.1 to 0.3% of Teflon based on the total weight of the core material; The chemical composition of the micro-carbon ferrochrome includes Cr: 63.0-75.0%, C≤0.03, Si≤1.0, P≤0.03, and S≤0.
025.
2. The drug core material according to claim 1, characterized in that: The rutile is 5 to 7 parts.
3. The drug core material according to claim 1, characterized in that: The reduced iron powder is 20 to 26 parts.
4. The drug core material according to claim 1, characterized in that: The micro-carbon ferrochrome is 15 to 17 parts.
5. The drug core material according to claim 1, characterized in that: The zircon sand is 19 to 20 parts.
6. A stainless steel welding wire, comprising a steel strip outer skin and a flux core, characterized in that: The core is made of the core material as claimed in claim 1, and the core material is filled in the outer skin of the steel strip. The outer skin of the steel strip is a 308L stainless steel strip. Based on the total mass of the 308L stainless steel strip, the 308L stainless steel strip includes the following components in percentage by mass: C: ≤0.03%, Mn: ≤2.00%, Si: ≤1.00%, Cr: 19.0-21.0%, Ni: 10.0-12.5%, P: ≤0.045%, S: ≤0.03%, and the remainder is Fe and unavoidable impurities.
7. The stainless steel welding wire according to claim 6, characterized in that: The filling factor of the drug core material is 20-25%.
8. A method for preparing a stainless steel welding wire as claimed in claim 6 or 7, characterized in that: The preparation steps include: S1, drying the components of the drug core material for the first time, adding the drug core material after the first drying into a powder mixer and stirring and mixing evenly, and then drying the evenly mixed drug core material for the second time to obtain a drug core material dry powder mixture; S2, rolling the steel strip into a U-shaped groove; S3, filling the drug core material dry powder mixture into the U-shaped groove; S4, closing the U-shaped groove containing the dry powder mixture of the flux core material, rolling it into an O-shape, and then drawing it to a set diameter of the stainless steel welding wire.
9. The method for preparing the stainless steel welding wire according to claim 8, characterized in that: In step S1, the temperature for the first drying of rutile, zircon sand, feldspar and cryolite is 900-950°C, and the drying time is 10-12 hours. The temperature for the first drying of reduced iron powder, micro-carbon ferrochrome, metallic chromium, metallic manganese, nickel powder, potassium fluorosilicate, rare earth fluoride and Teflon is 250-350°C, and the drying time is 10-15 hours.
10. The method for preparing the stainless steel welding wire according to claim 8, characterized in that: In step S1, the temperature of the mixed core material for the second drying is 100-150° C., and the drying time is 1-2 hours.
Citation Information
Patent Citations
Flux-cored wire for austenitic stainless steel all-position welding
CN102229029A
309(L) stainless steel flux-cored wire for thin plate welding
CN106736032A
Flux-cored material, seamless flux-cored wire and manufacturing method
CN114055016A